Liquid Crystal Semiconductors - นานันท์, สุวัตร (KKU Science Journal, 2013)
The calamitic liquid crystals based on rod-like molecules have been recognised for over 100 years. Not only their phase are well studied but their application are also well established, widly recognised as liquid crystal displays (LCDs). On the contrary, the mesophase formed by disc-like molecules, called discotic liquid crystals (DLCs), have only known for a little over 30 years since the discovery of these liquid crystals in 1977 by Chandrasekhar. The simplest mesophase found in DLCs is the nematic phase and the higher order phases can be formed as well namely, columnar phase, helical phase, and columnar plastic crystal phase. The structure of DLCs consists of two parts: the central aromatic core, the conducting part, and the alkyl chain, the insulating part. In this work, the applications of DLCs as semiconductors in electronic devices such as Organic Light-Emitting Diodes (OLEDs), Organic Field-Effect Transistor (OFET), and organic solar cell are summarised. The conductivity measurements of these materials from various methods namely chemical doping, current-voltage characterisation, PR-TRMC and ToF methods, have been reviewed.